Using Fishbone Diagram to Teach Writing Discussion Text to Senior High School Students - Silaban, Febri Rotama (Pascasarjana Universitas HKBP Nommensen, 2020)
Discussion text is one of the texts taught in SeniorHighSchool. Students often find it is difficult to understand the text. Fishbone diagram is diagram showing two side of view which is contrasted each other. Due to its structure which contains of two parts, this diagram can also be used in organizing ideas before writing a discussion text.In order to teach discussion text by using fishbone diagram, the writer uses four steps of teaching. First, teacher gives template of fishbone diagram to the students. Second, teacher asks students to start writing the first draft of discussion text. Third, students compare with friends what they have written. Fourth, the teacher guides students to check their friends’ work. In conclusion, fishbone diagram can help teacher in teaching writing a discussion text to the students.